Adherence to ART among Pregnant Women Living with HIV/AIDS in Lusaka Urban - Nthala, Victoria; Makasa, Mpundu; Hazeemba, Alice; Sitali, Doreen (Journal of Public Health International, 2019)
Introduction Adherence to ART is a challenge among pregnant women living with HIV/AIDS. This has an effect on the health of the mother and the unborn child. While studies have been done, it has shown that adherence during pregnancy is a challenge Virological and clinical success depend critically on high adherence to ART because with low adherence. The success of expanded ART coverage in improving health outcomes depends on adherence to treatment. During pregnancy, a compromised Virological response to ART also increases risk of mother-to-child transmission (MTCT) of HIV. This study was carried out to determine factors that influence adherence to antiretroviral therapy among HIV positive pregnant women in Lusaka district of Zambia. Methodology This was a qualitative study which used a case study approach. Data was collected through in-depth interviews. The collected data was analysed using a thematic analytical approach. Results 17 pregnant women living with HIV /AIDS in Lusaka had Challenges with adherence to ART. The study explored factors related to adherence to ART among pregnant women living with HIV/AIDS. ART adherence was found to be low. The findings call for the need to reduce on social stigma. The results confirmed that there is low adherence to ART among pregnant women living with HIV /AIDS in Lusaka. Conclusion Adherence to ART among pregnant women living with HIV/AIDS is a challenge for Zambian pregnant women. Improved levels of adherence to ART is hampered by fear of social stigma, and fear of being blamed by partners if they disclosed their status. Stigmatisation needs to be addressed because nearly all the participants expressed this factor. There is need to address the HIV/AIDS stigma very seriously in order for society to look at HIV/AIDS like any other illness.
Keywords: Adherence; ART; Pregnant women; living with HIV/AIDS; Social stigma